Energy expenditure by elite midget male ice hockey players in small-sided games. Issue 4 (August 2017) - Lachaume, Charles-Mathieu; Trudeau, François; Lemoyne, Jean
The purpose of this study was to investigate the energy expenditure and heart rate responses elicited in elite male midget ice hockey players during small-sided games. Nine players (aged 15.89 ± 0.33 years) participated in the study. Maximal progressive treadmill testing in the laboratory measured the relationship of oxygen consumption (V · O 2 ) to heart rate before on-ice assessments of heart rate during six different small-sided games: 1v1, 2v2, 2v2 with support player, 3v3 with support player, 3v3 with transitions, and 4v4 with two support players. Heart rate was recorded continuously in each game. 3v3 T small-sided game was the most intense for all four intensity markers. All six small-sided games reached 89% HRmax or more with heart rate peaks in active effort repetition. These findings demonstrate that such small-sided games are considered as high intensity games and are an effective training method for ice hockey players.